A Comparative Study of Material and Structural Configurations in Piezoelectric Energy Harvesting - Syed, Fahmidul Huq; Thong, Li Wah; Baig, Mirza Farrukh; Chan, Yee Kit; Efzan, M. N. Ervina (Ital Publication, 2025)
The objective of this study is to evaluate the energy harvesting performance of piezoelectric cantilever beams using three configurations—unimorph, bimorph, and stack—with two piezoelectric materials, PZT-5A and PVDF. The methodology involved a detailed analysis of voltage, mechanical power, and electrical power outputs across varying frequencies and load resistances. Experiments were conducted at the resonance frequencies of each beam configuration and material to determine their energy conversion efficiency. The results reveal that PZT-5A significantly outperformed PVDF, with PZT-5A's voltage output being up to 94% higher at resonance. Among the configurations, the bimorph beam with PZT-5A demonstrated the highest energy conversion efficiency, achieving a 50% increase in electrical power output compared to the unimorph configuration and a 9% improvement over the stack configuration. Load resistance analysis also indicated optimal energy harvesting in the range of 104 Ω to 105Ω. The novelty of this research lies in its comprehensive comparison of different materials and configurations, highlighting the critical role of structural design and material properties in optimizing piezoelectric energy harvesters for low-power applications. These findings provide valuable insights for improving the efficiency of piezoelectric devices in various practical applications. Doi: 10.28991/ESJ-2025-09-01-019 Full Text: PDF